NATO and Old Dominion University co-host disaster and incident management symposium. (4th September 2008) - McGinnis, Mike; Buck, Wayne
The 2008 Azalea Festival Symposium entitled, 'Katrina over Hampton roads: are we ready?' was held 15?16 April at Old Dominion University in Norfolk, Virginia and brought together over 250 attendees from 25 nations. Keynotes included Commissioner Jan Franssen, Queen's Commissioner for South Holland; Lieutenant General (Ret) Russel L. Honore, Former Commander, Joint Task Force Katrina; and Professor Eelco H. Dykstra, Professor of Emergency Management at George Washington University. The afternoon panel sessions featured discussions with state emergency management executives, federal officials, industry executives and academic subject matter experts. The panels were titled Emergency Management Policy and Coordination, Critical Infrastructure Resiliency and Evaluation of Human Impacts, and Emergency Management Training and Consequence Management. The symposium and resulting workshops generated a wide range of important observations and actionable recommendations for making the citizens and governments better prepared for dealing with all hazards incidents. Key recommendations were made in the areas of incident preparedness and response management, technology, emergency management policy, plans and processes, and individual and staff training and exercises will be used to inform the NATO countries, local, state and federal representatives and citizenry on actions that can be taken to create the 'culture of preparedness' that is needed.